The unnatural history of an atrial septal defect: Longitudinal 35 year follow up after surgical closure at young age. Issue 18 (25th July 2013) - Cuypers, Judith A A E; Opić, Petra; Menting, Myrthe E; Utens, Elisabeth M W J; Witsenburg, Maarten; Helbing, Wim A; van den Bosch, Annemien E; Ouhlous, Mohamed; van Domburg, Ron T; Meijboom, Folkert J; Bogers, Ad J J C; Roos-Hesselink, Jolien W
Abstract : Objective: To describe the very long-term outcome after surgical closure of an atrial septal defect (ASD). Design: Longitudinal cohort study of 135 consecutive patients who underwent surgical ASD repair at age <15 years between 1968 and 1980. The study protocol included ECG, echocardiography, exercise testing, N-terminal prohormone of brain natriuretic hormone, Holter monitoring and cardiac MRI. Main outcome measures: Survival, major events (cardiac reinterventions, stroke, symptomatic arrhythmia or heart failure) and ventricular function. Results: After 35 years (range 30–41), survival status was obtained in 131 of 135 patients (97%): five died (4%), including two sudden deaths in the last decade. Fourteen patients (16%) had symptomatic supraventricular tachyarrhythmias and six (6%) had a pacemaker implanted which was predicted by early postoperative arrhythmias. Two reoperations were performed. One ischaemic stroke occurred. Left ventricular (LV) and right ventricular (RV) ejection fractions (EF) were 58±7% and 51±6%, respectively. RVEF was diminished in 17 patients (31%) and in 11 (20%) the RV was dilated. Exercise capacity and quality of life were comparable to the normal population. No clear differences were found between ASD-II or sinus venosus type ASD. Conclusions: Very long-term outcome after surgical ASD closure in childhood shows good survival and low morbidity. Early surgical closure prevents pulmonary hypertension and reduces the occurrence of supraventricular arrhythmias. Early postoperative arrhythmias are predictive for the need for pacemaker implantation during early follow-up, but the rate of late pacemaker implantation remains low. Although RVEF was unexpectedly found to be decreased in one-third of patients, the functional status remains excellent.